Comportamiento agronómico del cultivo de maíz (zea mays l.) asociado con maní (arachis hypogaea l.) con diversos distanciamientos de siembra y tres dosis de bioestimulante orgánico. - Jiménez Jiménez, Ingris Elizabeth (2016)
The implementation of associated crops is becoming increasingly important because of the diversification of production as well as the opportunities they represent for the conservation and use of resources, adding to this the use of biostimulants as a means to increase the development and production of crops. Considering the aforementioned, the present investigation was carried out in order to determine the agronomic behavior of the association maize and peanuts planted to different plant spacings and doses of an organic biostimulant. The trial was conducted during the period June to October of 2016 on land of the property "Los Rocíos" owned by Mr. Napoleón Jiménez, located at km 16 of the road Quevedo - San Carlos. A randomized complete block design with factorial arrangement 3x3 + 3 was used in three replicates, studying three planting distances and three doses of the biostimulant bayfolan aktivator, whose interactions were compared with three controls. The Tukey test was used at 95% for comparison of means. As the main results, it was observed that with the 1.0 m sowing distance between rows of maize, longer ears (16.4 cm) were harvested and higher plants were obtained at 70 days (53.8 cm), higher Weight of 100 seeds (62.9 g) and higher yield per hectare (674.5 kg). When sowing maize at a distance of 1.2 m between rows, associated with peanut was recorded higher weight of grains per ear and more weight of 100 maize seeds with 203.2 and 36.8 g, respectively, while peanut cultivation produced longer pods (4.5 cm) and more pods per plant (26.1). Sowing at 1.0 m between rows of maize associated with peanut, yields increased corn yield per hectare with an average of 5104.5 kg / ha. The 1.5 l / ha dose of Bayfolan Aktivator allowed to obtain the longest ears, plants of greater height and greater yield of maize grain per hectare with averages of 16.5 g, 180.7 cm, 5177.3 kg / ha, and in the crop could Obtain longer pods (4.6 cm), and more pods per plant (26.3 pods). The 2.0 l / ha dose of Bayfolan Aktivator recorded greater weight of grains per ear and weight of 100 grains of maize with 188.0 and 36.5 grams, in their order, while peanut produced more harvested plants (33.4 plants), and Higher yield with 657.3 kg / Ha. The highest plants at 70 days and greater weight of 100 seeds were recorded with the dose of 2.5 l / ha of Bayfolan Aktivator, with averages of 53.5 cm, 60.8 g, in their order. Using the 1.0 m sowing distance between rows of maize and adding 2.0 l / ha of bayfolan aktivator, it produced a greater weight of 100 peanuts and a higher corn yield per hectare with 64.3 g and 5607.7 kg respectively. Sowing the maize to 1.2 m in rows and applying 2.5 l / ha of bayfolan aktivator, the highest peanut plants were obtained at 70 days with 55.1 cm. When sowing at 1.2 m distance between rows of maize and applying 1.5 l / ha of Bayfolan Aktivator in maize recorded higher weight of grains per ears with 205.4 g, while in peanuts it produced longer pods and greater number of pods per maize. Plant with 4.7 cm and 28.5 pods, in their order. Longer maize cobs were obtained when sowing at 1.0 and 1.1 m and applying 1.5 l / ha of bayfolan aktivator with 16.7 cm each. Sowing at 1.1 m between rows of maize, the highest maize plants were produced at 90 days with 183.4 days, and in turn this treatment recorded a higher weight of 100 grains as when sowed at 1.2 m between rows with the addition of 2.0 l / ha Bayfolan Aktivator, with 37.4 g each. When sowing at 1.0 m between rows of corn, a higher profit was achieved with $ 1574.69, ie a profit of $ 1.04 was obtained for every dollar invested.